Racialization, femininity, motherhood and the Iron Throne: Game of Thrones as a high fantasy rejection of women of color - Bollinger-Deters, Aaunterria Treil, author; Black, Ray, advisor; Kim, Joon, committee member; Chung, Hye Seung, committee member (Colorado State University. Libraries, 2018)
This analysis dissects the historic preconceptions by which American television has erased and evaded race and racialized gender, sexuality and class distinctions within high fantasy fiction by dissociation, systemic neglect and negating artistic responsibility, much like American social reality. This investigation of high fantasy creative fiction alongside its historically inherited framework of hierarchal violent oppressions sets a tone through racialized caste, fetishized gender and sexuality. With the cult classic television series, Game of Thrones (2011-2019) as example, portrayals of white and nonwhite racial patterns as they define womanhood and motherhood are dichotomized through a new visual culture critical lens called the Colonizers Template. This methodological evaluation is addressed through a three-pronged specified study of influential areas: the creators of Game of Thrones as high fantasy creative contributors, the context of Game of Thrones as a racially preoccupied high fantasy subgenre narrative, and the true implications of Game of Thrones social impact and mirroring even as a high fantasy entertainment venture. Through this deconstruction it is argued that: a) mimicry concerning racialized historical patterns present as artistic integrity through the agendas of the artists themselves b) Game of Thrones is a valid exhibition of inclusivity and progressiveness c) and a contemporary sociopolitical outline of the cycle of historical oppressions has been established through these creators of fiction, idyllically reinforced by their creations and affirmed by the dominant white societal structure which idolizes and imitates these specific forms of fiction; creating a justified thematic/political symbiosis in which historical politics feed fiction and vice versa. Through a constructed six points of contention, the Colonizers Template unsympathetically scrutinizes white masculinist supremacist creative structure through cinematic manipulations, signifying direct patterns of behavior in both the real world and the fictive creations made to reflect it. This analysis is conducted on the premise that Daenerys Targaryen is the identified strategic implementer of this template, through which both Eurocentric and patriarchal politics are evident as part of a larger institutional design in favor of whiteness. As a foundation of the racial spectrum to which the Colonizers Template evaluates gender performativity, sexuality politics, and status; Daenerys is positioned as the anchoring embodiment of white femininity and is investigated in two opposingly distinct stages: her rise to power and her maintenance of that power, with her marriage, rape, pregnancy, and her absorption of masculinist stations held by her brothers, husband, and son as the keys that grant her dualistic accessibility to both white masculinist entitlements and nonwhite cultural claims. With Daenerys as the white idyllic heroine of authoritative entitlement, her oppositional characterization becomes by default, the "othered" women of color within the Game of Thrones narrative who are vigilantly deconstructed through ideologies of blackness and Black femininity; reflecting an explicit designation of racialized thematic spaces as one of hierarchal stratagems. Through the deflective white feminine representation exhibited by centric protagonist Daenerys, the creative contradiction of thematic construction in the women of color who are advantageously presented as navigating varying stages of sociopolitical rejection remain in direct conflict with Daenerys positionality in terms of motherhood, vengeance, and justice. As high fantasy extensions of cultural differences and racialized designations, the fictive boundaries within Game of Thrones indicate these differences between three distinct groups: the Rhoynar, the Andals, and the First Men, through which a critical cross-examination of the disparate presentation of women of color is made accessible through geographical location, familial paradigm, death and fetishization demonstrated by the distinct narratives of Elia Martell of Dorne, Talisa Maegyr of Volantis, Ellaria Sand of Dorne and Missandei of Naath as evidence of racial variances and patterned weaponization of creative fiction as deeply interloping sociopolitical reality.